Modelos de teorías de colas para el análisis en los tiempos de atención en parqueaderos de centros comerciales de la ciudad de Barranquilla (2018)
In the present work of degree an analysis of the system of tails was carried out in the access to the parking of the Portal del Prado Shopping Center, based on the mathematical analysis of Theory of Tails, with the purpose of evaluating if the system satisfied the generated demand and proposing improvements according to the mathematical conclusions thrown by the model. For its development it was necessary to carry out a field study giving a quantitative and experimental approach to research. The model shows that the optimum number of servers for access to the parking lot on Calle 53 is four, compared to two servers that are currently used; Likewise, the optimal number of servers for access to the parking lot by race 50 is three, compared to two servers that are currently used. The results obtained by the model allowed to conclude that although the system presents an acceptable functioning, it has possibilities of improvement, which would allow to reduce even more the waiting times in its lines of access to the parking lot. It was also possible to conclude that the modeling methodology used was adequate for the analysis of these scenarios and that the model that was used (Model MMK) aptly describes the type of situations studied. This research will serve the interested public as a guide and consultation to develop their own studies. Likewise, it will serve as a methodology for the development of the Queue Analysis and Internal Operation section of the EDAU or ET, necessary to acquire the urban license in the city of Barranquilla.